The Relationship Between English and Polish Rhythm Measures in Polish Learners of English - Gralińska-Brawata, Anna (Research in Language, 2015)
This paper investigates native and non-native speech rhythm in the speech of Polish learners of English at an intermediate/upper-intermediate level. More specifically, it attempts to explore the relationship between rhythm measures scores in L1 Polish and L2 English within individual speakers. Phonological vowel reduction in terms of duration is present in English and crucial for the perception and acoustic measurements of linguistic rhythm. Polish, on the other hand, has no phonological reduction of that kind. The acquisition of L2 vowel reduction is highly determined by the level of language proficiency and influences non-native rhythmic patterns. The study tests six speech rhythm measures: %V, DV, DC, VarcoV, VarcoC and nPVI-V in two tempos: normal and fast. The results show that most of these measures are positively and significantly correlated with each other between L1 Polish and L2 English across the subjects and for two tempos, although to a different degree. Highly significantly correlation has been noted for %V and ΔC in fast tempo. Moderate significant correlations between the two languages are observed for ΔV, ΔC (normal tempo), VarcoV and nPVI in fast tempo.